The use of Panel Data to compare the impact of employment rates on development within the economic sectors in Syria (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The employment is the best way to face and reduce unemployment phenomenon, Many developed countries seek to achieve high levels of operation, with the aim of achieving more progress at various levels and achieving economic recovery, which benefits individuals and society, either. this study aims to highlight the comparison of the impact of employment  rates on the gross domestic product in the following economic sectors (industry, agriculture, construction and construction, hotels and restaurants, transportation, money and real estate, services)depending on the analysis of the panel data  conducting  the tests related to them to obtain a comparative model between the mentioned economic sectors and the most important results that we have reached are: employment rates contribute more than 50% to the changes that occur to the gross domestic product, and there is a difference between the cross sections properties of  The effect of employment rates on GDP. The most important thing this research recommended was to face the phenomenon of unemployment in all its forms, and to give more attention to human resources and energies, to focus on raising employment rates in various economic sectors.